Biochemical Characterisation of Different Male Morphotypes of Macrohrachium rosenbergii (De Man) - S., Suresh Kumar; B., Madhusoodana Kurup (Fishery Technology, 2025)
Protein, carbohydrate, lipid, DNA and RNA contents were studied in the muscle tissue, hepatopancreas and gonads of male morphotypes of M. rosenbergii viz. small males (SM), orange clawed males (OC) and blue clawed males (BC) and their transitional stages, weak orange clawed (WOC) and strong orange clawed (SOC). Significant difference could be seen in protein, DNA and RNA contents of muscle tissue, carbohydrate and RNA contents in hepatopancreas and DNA and RNA contents of the gonads of various male morphotypes. Highest protein content in muscle was recorded for SOC (19.10%) and minimum for WBC (17.71%) and OBC (17.52%). Highest values of RNA (1.020 mg/g) and DNA (0.68mg/g) of muscle tissue was also recorded in SOC. Carbohydrate content (2.37%) and RNA (0.744 mg/g) content of hepatopancreas were also found to be high in SOC when compared to other male morphotypes. In gonads highest DNA content (0.891 mg/g) was observed in OBC whereas RNA content was maximum in SBC (1.159 mg/g). Results of the present study would be useful in providing biochemical evidence for the existence of morphotypes in male populations of M. rosenbergii.